The structural basis of translational control by eIF2 phosphorylation - Tomas Adomavicius (Nature Portfolio, 2019)
During the integrated stress response, translation is modulated through the phosphorylation of translation initiation factor eIF2 and the formation of a complex with eIF2B. Here the authors present structures of the eIF2:eIF2B complex with and without phosphorylation, shedding light on how eIF2 phosphorylation regulates translation.